IBM Pavilion at night
Caption, "The Information Machine the main attraction of the IBM Pavilion at the 1964-65 New York World's Fair is shown at night. It consists of a 90 foot high ovoid theater and 12 tiers of seats which lift audiences into the theater for a dramatic presentation. The pavilion was designed to create a whole environment, rather than providing a building to house exhibits."